Review of Design and Implementation of the Agricultural Insurance Programs of the Philippine Crop Insurance Corporation - Christian D. Mina; Celia M. Reyes; Reneli Ann B. Gloria; Sarah Joy P. Mercado (Philippine Institute for Development Studies (PIDS), 2015)
The situation of the poor who participate in the country's agricultural sector has been exacerbated by the increasingly prevalent natural calamities, pests, and other such unpredictable event. However, there are certain risk management tools that aid in lessening the farmers' financial burden when losses related to such natural disasters are incurred. One of them is the crop or agricultural insurance. In the Philippines, the Philippine Crop Insurance Corporation (PCIC) is the government organization that implements rice, corn, high-value commercial crop, livestock, noncrop agricultural asset, fishery, and term insurance programs. The question thus arises regarding the effectiveness and sustainability of the said programs. It is thus the purpose of this study to review the design and implementation of the PCIC's insurance programs. Key informant interviews and focus group discussions with various PCIC clients and partners in selected regions of the country, together with desktop review and secondary data analysis, were conducted.
Keywords: 330; Philippines; agricultural insurance; Philippine Crop Insurance Corporation; design; implementation; process evaluation